2018
DOI: 10.1371/journal.pone.0198054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and drug resistance patterns of Mycobacterium tuberculosis complex isolates from university students and the local community in Eastern Ethiopia

Abstract: BackgroundPrevious studies suggest the burden of pulmonary tuberculosis (PTB) in Ethiopia may be greater in university students relative to the overall population. However, little is known about the transmission dynamics of PTB among students and members of the communities surrounding university campuses in Eastern Ethiopia.MethodsA cross sectional study was conducted in Eastern Ethiopia among prevalent culture-confirmed PTB cases from university students (n = 36) and community members diagnosed at one of four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
6
8
3
Order By: Relevance
“…The 15.9% (11/69) drug resistant detection rate using BACTEC MGIT 960 in this study was at greater proportion than similar studies [ 30 , 31 ]. On the contrary, less proportion of drug resistances were reported in this study than other research reports by using the same detection system [ 32 , 33 ] which might be due to different study areas and sample size. Most of the isolates detected as resistant by LPA were also resistant by MGIT.…”
Section: Discussioncontrasting
confidence: 93%
“…The 15.9% (11/69) drug resistant detection rate using BACTEC MGIT 960 in this study was at greater proportion than similar studies [ 30 , 31 ]. On the contrary, less proportion of drug resistances were reported in this study than other research reports by using the same detection system [ 32 , 33 ] which might be due to different study areas and sample size. Most of the isolates detected as resistant by LPA were also resistant by MGIT.…”
Section: Discussioncontrasting
confidence: 93%
“…In agreement with previous studies, the predominance of lineage 3 (Delhi/CAS; 32.1%) using MIRU-VNTR 24-loci genotyping showed its wide distribution throughout the country [10,50,51]. On the contrary, it was not the predominant strain rather H37Rv like and Ethiopia_3 were the most common sub-lineages in studies from prisoners and communities in Southern, Southwestern and Southeastern Ethiopia [52] and Eastern Ethiopia [32], respectively. This revealed that the overall predominant lineage of M. tb across the country varries.…”
Section: Molecular Epidemiology Of Tuberculosissupporting
confidence: 91%
“…The variation of spoligotype clustering in this study in comparison to many other reports might be due to the differences in geographical study settings. There were higher clustering rates reported from most studies in Ethiopia [30,32,33]. Similarly, studies outside of the country also reported greater proportion of clusters [34][35][36][37] than the overall clustering rate of this study 20.2% (21/104) which might be due to the poor recovery rate of smear positive bacteria on LJ-culture.…”
Section: Molecular Epidemiology Of Tuberculosiscontrasting
confidence: 53%
See 1 more Smart Citation
“…In other words, successful transmission of particular genotypes has been reflected through an increase in the frequency and consistency of strain domination over time in defined populations [16,23]. However, despite recently developed advanced molecular diagnostic tools, both the nature of genotype variations and the characteristics of the host immune response to certain types of M. tb strains are largely unknown in many TB high burden settings [24,25]. Particularly in countries like Ethiopia, where there is high prevalence and high transmission rate and a diversified population of bacterial species [26-29], molecular identification of the agents can be an important component of the knowledge base required to improve on previous achievements of the national TB control program.…”
Section: Introductionmentioning
confidence: 99%